2022
DOI: 10.3390/jcm11216478
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in COVID-19 Outpatients: A Long-Term Follow-Up Study

Abstract: Background: The long-term issues faced by COVID-19 survivors remain unclear. Symptoms may persist for several months, even in non-hospitalized patients, probably impacting the quality of life. Objective: To assess the health-related quality of life of outpatients one year after SARS-CoV-2 infection. Design, Settings, and Participants: This prospective multicentre study, conducted in France from February 2020 to February 2022, compared 150 COVID-19 cases (PCR+ and/or CT scan+) and 260 controls (PCR-) selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…As displayed in Table 1, the current systematic review comprised 20 studies representing a variety of countries. Each of the subsequent countries had one research conducted: Sweden [35], Switzerland [27], Germany[16], Italy [17], Slovakia [23], Norwegian [29], France [32], Netherlands [33], Denmark [25], and Spain [28]. Two studies were done in Norway [20,30], while another 2 studies were reported in Israeli [19,24], four studies were performed in the UK [21,22,26,31] and one study in the USA [18].…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As displayed in Table 1, the current systematic review comprised 20 studies representing a variety of countries. Each of the subsequent countries had one research conducted: Sweden [35], Switzerland [27], Germany[16], Italy [17], Slovakia [23], Norwegian [29], France [32], Netherlands [33], Denmark [25], and Spain [28]. Two studies were done in Norway [20,30], while another 2 studies were reported in Israeli [19,24], four studies were performed in the UK [21,22,26,31] and one study in the USA [18].…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, other studies conducted comprehensive 7-month, 9month, and 10-month follow-up periods, [16, 19,23]. Effectively, more studies focused on the long-term progression of the condition [20,28,32]. Some studies implemented a exible approach toward follow-up and had a follow-up period of 6-12 months, 3-8 months, and 3-5 months [18, 24,30].…”
Section: Follow-up Since Covid-19 Onsetmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and burden of long COVID increase with the severity of acute disease 11 , but it also occurs in patients with mild symptoms who do not require hospitalization 12 . Long COVID has been shown to negatively impact quality of life 13 , 14 and can persist for a long time after infection 15 . Investigations into the long-term effects of COVID-19 beyond 2 years are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Even in non-hospitalized workers, COVID has affected the health of the victims, and its post-sequelae has been less studied. Persistence of symptoms post-COVID, especially chest symptoms like early fatigue with breathlessness, has been documented very well [ 2 , 3 ]. A study done by Lee et al in China has shown that in re-confirmed cases of COVID-19, physical symptoms after quarantine persisted along with feelings of depression and psychological stress.…”
Section: Introductionmentioning
confidence: 99%